Kinematic analysis and experiment of planetary five-bar planting mechanism for zero-speed transplanting on mulch film - Jiaodi, Liu; Weibin, Cao; Dongyang, Tian; Haiyang, Tang; Hongzheng, Zhao (International Journal of Agricultural and Biological Engineering, 2016)
A novel seedling transplanting mechanism with planetary five-bar was developed in order to solve some problems when transplanting seedlings on mulch film, such as a large cave diameter, a low proportion of upright seedlings, and inconsistent planting depths, which seriously restrict the development of transplanting equipment used in dryland agriculture. The planetary five-bar structure of transplanting mechanism was designed based on analysis of the seedling transplanter on mulch film. The kinematics model of the transplanting mechanism was established and the optimal parameters of the transplanting mechanism were obtained by satisfying the motion trajectory conditions. Subsequently, the virtual prototype of transplanting mechanism was developed, and the simulation of motion trajectory was illustrated. Finally, the physical prototype of the transplanting mechanism was assembled and tested with the high-speed photography. The simulation results indicated that the desired “spindle” trajectory for the duckbill can be obtained, of which the height was 350 mm, and the diameter of the planting cave was 32 mm. The experimental results showed that the diameter of the planting cave was less than 70 mm, the seedling perpendicularity qualification rate reached 96%, the film injury rate was less than 0.5%, and the hanging membrane phenomenon was avoided. Therefore, the proposed transplanting mechanism can meet the requirements for a mulch-film transplanting machine. Keywords: seedling transplanting, mulch-film, planetary five-bar mechanism, zero-speed transplanting, parameter optimization DOI: 10.3965/j.ijabe.20160904.2073 Citation: Liu J D, Cao W B, Tian D Y, Tang H Y, Zhao H Z. Kinematic analysis and experiment of planetary five-bar planting mechanism for zero-speed transplanting on mulch film. Int J Agric & Biol Eng, 2016; 9(4): 84－91.